The canonical concept of the juridical act. An introduction for civil lawyers - Skonieczny, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The author gives a general presentation of the canonical concept of the juridical act (cf. canons 124–127 CIC). He indicates its theological and anthropological basis (the person and the actus humanus) as well as its sources in the European juridical tradition. According to the author, in the canonical system the juridical act is a human act (actus humanus) that is a conventional act (a formal act), and it results in certain specific and desired legal effects. The canonical concept of the juridical act is regulated by three rules: the rule of personalism (the emphasis on its personal character), the rule of universality (the extented scope of the application of this term also to public acts), and the rule of permanence (the continuance of the juridical act).